The role of nostalgia in reality television’s representation of rural lives - Edwards, Abigail (Centre for Film and Media Studies, 2020)
This dissertation examines the role of nostalgia in reality television’s representation of rural lives. My study merges a theoretical and critical investigation. I take Alaska: The Last Frontier as my case study and argue that the programme responds to social change and urban living conditions in the United States by creating a nostalgic and idealistic representation of preindustrial American life. While the text is largely reactionary and calls upon a restorative nostalgia that imagines ideal American life as rural, white and heteronormative, the show also exhibits elements of reflective nostalgia, using the Kilcher family’s lifestyle to critique contemporary late capitalist lifestyles. Furthermore, I argue that this use of nostalgia conveys a dissatisfaction with post-industrial and urban life by foregrounding an idealistic settler narrative that implies it is not through progressive reform that America will find its nostrum but through a return to conservative values. The chapters in this thesis examine aspects of contemporary urban life that have drastically changed since the onset of America’s industrial revolution. My first chapter argues that nostalgia can manifest in an individual and potentially, a nation. I also argue that reality television plays a significant role in evoking nostalgia and uses it to respond to the sociological conditions of late capitalist urban life. Chapter 2 explores the relationship between the wilderness and nostalgia. In particular, I consider how the 'frontier myth’ structures the show’s nostalgic representation of rural living. In my third chapter I discuss how Alaska: The Last Frontier evokes nostalgia for a lost sense of kinship and community, reminiscent of a preindustrial revolution American culture. This chapter also uses the condition of anomie to further understand how the seemingly disparate relationship between the urban setting in which the programme is largely consumed and the nostalgia for a sense of family and community that the programme evokes, relate. Chapter 4 argues that the representation of labour in Alaska: The Last Frontier constructs a 'fantasy of wholeness’ and that this process potentially evokes nostalgia for an idealised set of labour relations that are perceived to be lost in the late capitalist age. I present a case study from Alaska: The Last Frontier to show how the programme constructs a 'fantasy of wholeness’ through representing idealised labour relations that are in stark contrast to Marx’s theory on how capitalist labour conditions are experienced. Finally, my fifth chapter reflects on the complex and integral role that nostalgia plays in Alaska: The Last Frontier’s representation of rural lives and discusses how the work I have presented in this thesis may provide a basis for future enquiries.